g(a) -> g(b)

b -> f(a, a)

f(a, a) -> g(d)

R

↳Dependency Pair Analysis

G(a) -> G(b)

G(a) -> B

B -> F(a, a)

F(a, a) -> G(d)

Furthermore,

R

↳DPs

→DP Problem 1

↳Narrowing Transformation

**G(a) -> G(b)**

g(a) -> g(b)

b -> f(a, a)

f(a, a) -> g(d)

On this DP problem, a Narrowing SCC transformation can be performed.

As a result of transforming the rule

one new Dependency Pair is created:

G(a) -> G(b)

G(a) -> G(f(a, a))

The transformation is resulting in one new DP problem:

R

↳DPs

→DP Problem 1

↳Nar

→DP Problem 2

↳Narrowing Transformation

**G(a) -> G(f(a, a))**

g(a) -> g(b)

b -> f(a, a)

f(a, a) -> g(d)

On this DP problem, a Narrowing SCC transformation can be performed.

As a result of transforming the rule

one new Dependency Pair is created:

G(a) -> G(f(a, a))

G(a) -> G(g(d))

The transformation is resulting in one new DP problem:

R

↳DPs

→DP Problem 1

↳Nar

→DP Problem 2

↳Nar

...

→DP Problem 3

↳Narrowing Transformation

**G(a) -> G(g(d))**

g(a) -> g(b)

b -> f(a, a)

f(a, a) -> g(d)

On this DP problem, a Narrowing SCC transformation can be performed.

As a result of transforming the rule

no new Dependency Pairs are created.

G(a) -> G(g(d))

The transformation is resulting in no new DP problems.

Duration:

0:00 minutes